(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Prednisolone is the 1st choice of drug in Idiopathic Nephrotic Syndrome (INS). Deflazacort (DFZ) is a new step in this regard. Aim of this study was to compare the efficacy of prednisolone and DFZ in children with INS. Materials and methods: 76 children of 2-16 years with INS were enrolled in a Randomized Controlled Trial (RCT). Patients were randomized to either group-A (DFZ) or group-B (Prednisolone) and 38 children were allocated in each groups. After giving treatment with both drugs, these patients were followed up at 3 months interval for 2 times to compare the clinical effects. Due to lost follow up finally 65 patients were analyzed. Data was documented on pre-structured data sheet and analyzed by SPSS version 22.0. Chi square test for categorical data and unpaired ttest for continuous data were done. A probability (p) value < 0.05 was considered statistically significant. Results: Mean time to get remission was 5.32±1.28 days in DFZ group and 8.00±2.55 days in prednisolone group. It was statistical significant (p= <0.001). Mean duration of remission was 171.29±19.27 days and 146.66±54.61 days in Group A and Group B respectively and was statistically significant (p= 0.020). Total number of relapse by treatment with DFZ is less in comparison of prednisolone. Conclusion: DFZ was more effective as shorter time was required to induce remission and achieved remission was maintained for longer durationin INS. Number of relapse by using DFZ was less than prednisolone. Number with no relapse were more in DFZ than prednisolone on follow up time. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 18-21